Minette's feast : the delicious story of Julia Child and her cat - Reich, Susanna (Abrams Books for Young Readers, 2012)
While Julia is in the kitchen learning to cook up elaborate, delicious dishes, the only feast Minette is truly interested in is that of fresh mouse. Includes biographical information about Julia Child.